IMPROVEMENT OF SEED VIABILITY AND VIGOR OF SEVERAL RICE VARIETIES WITH VARIOUS PRIMING METHODS - Putri, Sheila Izdihar Hendra; Suwignyo, Rujito Agus; Negara, Zaidan Panji; Sulaiman, Firdaus; Irmawati, Irmawati (Biology Department, Faculty of Mathematics and Natural Sciences, Sriwijaya University, 2023)
Rice serves as Indonesia's main food source, but inadequate storage conditions can lead to seed deterioration and diminished germination performance. To enhance the viability and vigor of stored seeds, this study explores various priming methods' effects on multiple rice varieties. Employing a completely randomized design (CRD) with two factors, the first factor involves rice varieties (V) categorized by germination ranges: 41–50% (V1 = Toyonishiki, V2 = Yoneshiro), 51–60% (V3 = Jaya, V4 = IR50), 61–70% (V5 = Fortuna, V6 = Sulutan), and 71–80% (V7 = IR 24, V8 = Inpago 5). The second factor is seed priming (P), including control, hydropriming, and osmopriming. Results indicate that priming enhances maximum growth potential, germination percentage, vigor index, growth speed, plumule and radicle length, as well as fresh and dry weight. Hydropriming outperforms osmopriming, particularly in vigor index, growth speed, plumule and radicle length, and dry weight. Priming proves more effective in improving maximum growth potential, germination percentage, vigor index, and growth speed at lower germination percentage ranges (41–60%). The most significant priming-induced increases in radicle length, fresh weight, and dry weight occur in higher germination percentage ranges (61–80%)